A COMPREHENSIVE STUDY OF ASHMARI IN BRIHATTRAYI - Kumar, *Bishnu; Singh, Jyoti (AYUSHDHARA, 2017)
From the study of ancient surgical text Sushruta samhita, it becomes evident that the urological problems form an important part of medical sciences. Among all the urinary problems described in Ayurvedic texts, there is one variety where both the medicinal and the surgical treatments are advised and agreed upon by all the Acharyas and this entity is the Mutrashmari. Ashmari is one of the most common and distressing disease among the group of urinary disorder. In the ancient period the diagnosis of Ashmari was done, based only on the Lakshanas. The sufficiency of clinical features alone to make diagnosis is difficult. In the current practice, the diagnosis is based only on imaging techniques, which has enhanced the diagnostic capability of the disease. This article reviews the various concept of Ashmari in Brihattrayi regarding its classification, symptomatology, etiological factors, pathology, complications and management have been dealt with both medico-surgical procedure. It is an attempt to compile the various concept of Ashmari disorders scattered in Brihattrayi and correlate them with modern urinary disorders.